Obesity, Weight Management and Diagnosis in Women - Metwally, Nourhan Mohamed; Seif, Mai Hassan (Cardiology and Cardiovascular Medicine, 2021)
In the United States and around the globe, obesity is a primary cause of disease and death. Obesity is a chronic disease that is commonly seen in clinical practice today, and it necessitates a variety of medical treatments. Obesity affects both males and females of all ages, but there are some factors that are particularly relevant to women’s health. Obesity is more common among women in the U.S. than it is amongst men. To lower the incidence of obesity, effective interventions are required. The success of contemporary weight loss strategies, however, varies. This article provides practical advice on how to manage your lifestyle. These approaches can assist females in setting more realistic weight loss goals, adapting to patient-specific lifestyle counselling, and implementing ways to improve compliance for longterm weight loss.